"Target Heart Rate" calculated aiming at zero overlap of mitral E and A waves is useful for prediction of long-term outcome for patients with heart failure and reduced ejection fraction. (14th October 2021) - Yumita, Y; Nagatomo, Y; Takei, M; Saji, M; Goda, A; Kohno, T; Nakano, S; Nishihata, Y; Ikegami, Y; Shiraishi, Y; Kohsaka, S; Yoshikawa, T; et al.
Abstract: Background: Lower heart rate (HR) is associated with more favourable long-term outcome in patients with heart failure with reduced ejection fraction (HFrEF). However, an optimal threshold of HR remains unclear. Targeted HR (THR), defined by echocardiographic deceleration time (DCT) to eliminated overlap of E and A waves, may aid in risk stratification of HFrEF patients. Purpose: In this study, we aimed to clarify the impact of on long-term clinical outcome in patients with HFrEF. Methods: In the multicenter WET-HF registry, 4000 consecutive patients hospitalized for acute decompensated HF (ADHF) were registered between 2006 and 2017. Among them, the patients with EF ≥40% or a history of atrial fibrillation were excluded. THR was calculated based on their DCT value measured in compensated HF phase during the index admission. The following formula was applied; THR (bpm)=93 - 0.13 × deceleration time (DCT, msec). A total of 876 patients with HFrEF were included in the present analysis (age: 72 [60–81], male: 69%) and the patients were divided into the 2 groups of HR at discharge ≤ THR (L group) and > THR (H group). The primary endpoint (PE) was defined as the composite of all-cause death and ADHF re-admission. Results: Compared to the H group, the L group showed higher prevalence of males (74% vs. 66%, P=0.025) with higher body mass index (BMI, 23.2 vs. 22.2, P=0.016), hemoglobin (Hb, 12.9 vs. 12.4, P=0.031), albumin (Alb, 3.7 vs. 3.6, P=0.039) and larger left atrial diameter (LAD, 44 mm vs. 41 mm, P=0.002) and tricuspid regurgitation pressure gradient (TRPG, 29 mmHg vs. 27 mmHg, P=0.012). Age, estimated glomerular filtration rate (eGFR), LVEF (29% vs. 30%, P=NS) and E/e' (17.7 vs. 16.8, P=NS) were similar for both groups. At discharge, HR was lower in L group (66 [60–71] bpm vs. 80 [74–86] bpm, P<0.001), albeit there were no significant differences in b-blocker prescription (90% vs. 85%, P=0.069) or its dose (3.75 [1.25–7.25] mg vs. 2.5 [1.25–5] mg, P=0.11). In the survival analysis, the L group showed a significantly lower rate of PE (P=0.03), whereas there was no significant difference in the incidence of PE between the patients with HR at discharge ≥70 bpm and <70 bpm (P=NS). Multivariate Cox hazard analysis showed that HR at discharge ≤ THR was an independent predictor of PE (hazard ratio 0.67 [0.46–0.97], P=0.037), even after adjusting for confounding factors including age, sex, BMI, Hb, Alb, and b-blocker prescription, whereas HR at discharge <70 bpm was not (hazard ratio 0.94 [0.65–1.33], P=0.71). Conclusion: THR was associated with long-term outcomes in patients with HFrEF after acute decompensation, suggesting that it may aid in tailored treatment for HR reduction in these patients. Funding Acknowledgement: Type of funding sources: None.